Etude De L’efficacité Du Cashew Nut Shell Liquid (CNSL) De Anacardium Occidentale L. Extrait À Froid Sur Le Contrôle De Anopheles Gambiae S.L Résistant Aux Pyréthrinoïdes - Akpo, Armand A.; Chougourou, Daniel C.; Djènontin, Armel; Dossou, Joseph; Anagonou, Rodrigue; Akogbéto, Martin (European Scientific Journal, ESJ, 2017)
In order to combat the vectors of malaria, it is necessary to know their behavior with regard to the insecticide products envisaged. The present study is aimed at the CNSL efficiency test extracted from the seed hull of Anacardium occidentale L. for the control of pyrethroid-resistant Anopheles gambiae s.l. Sensitivity tests were carried out on the larvae of stages 2, 3 and 4 of An. gambiae of the wild and Kis-kdr strains carrying the Kdr gene. The "Kisumu" strain devoid of resistance gene served as a control. The mortalities were read after 24 hours of exposure. LD50 and DL90 were determined using the log-probit method of dose determination corresponding to a proportion. The high LD50 determined is 0.0042 mg / ml and corresponds to the LD50 of the larvae of stage 2 of the wild strain. The low LD50 is determined on stage 2 larvae "Kisumu". The high DL90 is determined on stage 4 larvae of the wild strain. The low LD90 determined corresponds to stage 2 larvae "Kisumu". The comparison of the LD between the different strains shows a low sensitivity to CNSL of the larvae of resistant strains compared to the control strain, indicating the influence of the resistance factor kdr on the CNSL efficiency. However, the low-dose CNSL larvicidal activity on the larvae of the kdr-carrying strains provides an alternative advantage in the management of vector resistance to pyrethroids